Study on Process of Converting Wind Energy to Electricity: https://doi.org/10.69692/SUJMRD0802228 - BOUNTHONG, Bounseng; KEOMANICHANH1, Phonepadith (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
Wind is a renewable energy, wind is product natural from the change of air temperature, air pressor and the rotate of planet. Wind is an old source of energy so the humans was use it for wind mill, sailing, air transport or drying and so on. Now a day, many countries are focusing on research study about wind turbine to generate electricity. The purpose of this research is to study the process of converting wind energy into electricity by taking wind source from a fan with a radius of 17 cm, the fan speed is about and the wind turbine power source is a small motor model ESPL-3423-D120. The study shows that the efficiency of wind turbines from the conversion of kinetic energy into electricity is about 15%. For radius of wind turbines 15 cm, we can convert wind power into electric power about 0.8954 W; For radius of wind turbines 17 cm, we can convert wind power into electric power about 1.1454 W; we also notice that the wind power is change by a radius of wind turbine and wind speed